Kualitas Kertas Seni Dari Pelepah Tanaman Salak Melalui Biochemical Kultur Campuran Phanerochaete Crysosporium Dan Pleurotus Ostreatus Dengan Variasi Konsentrasi Naoh - Fahmi, M Saiful; , Efri Roziaty, M.Si (2016)
Art paper is generally made using a chemical process (chemical pulping) and mechanical (mechanical pulping). This reseacrh aims to determine quality art paper from the stem bark of plants through Biochemical mixed culture Phanerochaete crysosporium and Pleurotus ostreatus with various concentrations of NaOH. The method used in this study is an experimental research using the completely randomized design (CRD) with two factors: the long incubation (L) and the variation of the concentration of NaOH (N). long incubation for 30 days (L1) and the long incubation of 45 days (L2). Then the second factor concentration of NaOH (N) with a concentration of 10% (N1) and a concentration of 15% (N2). The parameters in this research is the tensile strenght of art paper, break force art paper and art sensory test (texture, color, fiber appearance and acceptance of the public) are made from the midrib bark. The results showed that the use Biochemical using white rot fungus effective for paper making art with the best results in treatment N2L2 (NaOH concentration of 15% and a long incubation of 30 days with JPP) to tensile strenght for 0.24 K / m2 and break force power by 18 , 71 N compared with control treatment N2L0 (NaOH concentration of 15% without incubation JPP) which has a tensile strength of 0.13 K / m2 and break force of 12.11 N. So it can be concluded that the bio-chemical can be used as an alternative in papermaking art.